PENERAPAN E-FAKTUR SEBAGAI PERBAIKAN SISTEM ADMINISTRASI PPN (Persepsi Kantor Konsultan Pajak X ) - Permata Sari, Selfi Ayu; Pusposari, Devi (Jurnal Ilmiah Mahasiswa FEB, 2015)
From July 1st 1984 until July 1st 2015, manual tax invoices was still used by some Tax Payer. However, in practice a lot of abuse in the form of tax invoice emergence of fictitious tax invoices, double tax invoices, as well as the disability tax invoice. Numbers of tax invoice abusement, high cost of compliance, and the burden of government oversight is the reason for applying e-Invoicing. On July 1st  2015, the use of electronic tax invoices using e-Invoicing applications was required by government in Java and Bali. This research has purpose to determine the e-Invoicing applications as the improvement of the administration of the VAT system from the standpoint of the Tax Consulting Firm X. The results of this research has show that the e-Invoicing has strengths and weaknesses in its application. The strengths of e-Invoicing is that it can be more effective and efficient in manufacturing as well as transaction of tax invoice. While the weakness of e-Invoicing applications is a way of working is more complicated than the manual invoicing tax and previous VAT returns application. Additionally, from 7 causes correction periodic VAT return conducted by CTF client X, 5 of them can be reduced or prevented by the e-Invoicing application.   Keywords: Tax Consulting Firm, Manual Tax Invoice, Application of e-Faktur, Periodic VAT Return.